"Deny all knowledge" reading The X-Files - Lavery, David; Hague, Angela; Cartwright, Marla (Faber and Faber, 1996)
The X-Files has taken Britain and America by storm. Deny All Knowledge examines why the series is such a success at this time in our history, and asks whether its conspiracy plot provides an indication of the political state of America.